Hydrodynamic studies of well No 32 the southern section of the Chinarev field of the West Kazakhstan Region - Satayeva Sapura; Urazova Aliya; Kiisheva Dinara; Mendygaliyeva Aigul (E3S Web of Conferences, 2024)
The article analyzes the factors influencing the development of high-quality and cost-effective oil and gas reserves in the region (assessment, design). In order to operate wells, directions for calculating the size of reserves have been found. Scientific and technical trends of its (wells) development are considered. A comprehensive analysis of integrated surveys was carried out at well No.32 of the Chinarevsk oil and gas condensate field, located in the southern section of the district. Hydrodynamic studies were carried out by interpreting the pressure recovery curve (PRC) to determine reservoir pressure, porosity and reservoir properties of the reservoir and the state of the bottom whole zone. These studies confirmed the low porosity properties of the reservoir: permeability - 0.004 μm2, conductivity - 0.056 μm2*m, hydraulic conductivity - 0.055 μm2*m/mPa*s. The skin factor varied in the range from -0.92 to 18.4, which indicates deterioration in the state of the bottom hole formation zone.